Talus dislocation and pereonal malleolar fracture after high-energy trauma: a case report - Pedrazzini, Alessio; Casalini, Daniele; Bertani, Chiara; Yewo Simo, Henri; Bisaschi, Roberto; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2023)
Talus dislocation is a rare injury and it is usually the consequence of high energy traumas, despite the anatomical features of the talus which predispose to its dissociation (absence of muscle insertions with over 60% of the surface covered by cartilage). It may be associated with malleolar fractures. Standard treatment of closed talar dislocation is a controversial issue. The most common early complications is avascular necrosis. Authors report a case of a complete talar dislocation associated to displaced lateral malleolar fracture in a 18-years-old male following a high energy trauma treated by closed reduction and fixation of the malleolar fracture.